Being “Nutritionally at Risk”: Its Effect on Health Expenses and Length of Hospital Stay: Nutritional Risk: Health Expenses and Length of Hospital Stay - Güngör, Anıl Evrim; Kılınç, Fatma Nişancı; Alparslan, İrem and Çakır, Biriz and Asil, Esma and Esatoğlu, A. Ezel and Yavuz, Yasemin and Demirer, Seher (Progress in Nutrition, 2022)
Objective: Hospital malnutrition is a critical, cost-increasing public health problem that is common in many countries. The study aimed to evaluate the effect of “being nutritionally at risk” on health expenses and length of stay (LOS) in hospital. Material and Method: Nutritional Risk Screening-2002 (NRS-2002) was used to screen 1069 adult patients on admission day. Patients’ anthropometric measurements, unintentional weight loss, hand grip strength (HGS), cancer diagnosis, as well as LOS were recorded. Health expenses for each patient was obtained from hospital billing system. Results: Of the patients, 19.1% had NRS-2002³3 (nutritionally at risk) which was more frequent among male patients (61.8%) than female patients (38.2%) (p<0.001). The odds of being nutritionally at risk increased by 1.029 times with one year increase in age (p<0.05). The median of HGS was lower in patients with NRS-2002³3 (p<0.05). Patients without nutritional risk (NRS-2002<3) had a LOS of 7.65±7.61 days, while corresponding figure was 16.5±15.64 days for patients with NRS-2002³3 (p<0.001). Patients’ health expenses with NRS-2002<3 and NRS-2002³3 were 384.19 and 873.89, respectively (p<0.01). One percent increase in involuntary weight loss and one unit decrease in HGS resulted in 2588 and 1066 increase in average expenses, respectively (p<0.05). The odds of becoming NRS-2002≥3 increased 1.566 times with 1% increase of involuntary weight loss (p<0.001). Cancer patients whose average LOS was 4.5 days longer had 4.93 times increased risk of developing nutritional risk during hospital stay (p<0.001). Conclusion: Nutritional status of patients should be assessed during hospitalization. Patients with nutritional risk have higher total costs and stay longer in the hospital than the patients with no risk.